Etiology and Demographic Profile of Medico-legal Cases in Emergency of a University Hospital in Nepal - Khatri, Pratima; Munikar, Anita; Pandit, Pooja; Rai, Lalita; Maharjan, Ramesh K; Sharma, Mohan R (Journal of Institute of Medicine Nepal, 2022)
Introduction Any injury or ailment where investigations by the law-enforcing agencies are crucial are considered as medico-legal cases. The objective of this study was to describe the profile of medico-legal cases presented to the Emergency Room (ER) of Tribhuvan University Teaching Hospital (TUTH), Kathmandu, Nepal. Methods A retrospective review of medical records was done to include all medico-legal cases presented from July 2018 to June 2019. Results Medico-legal cases comprised 1805 (3.8%) of all cases (47,289) in the study period. The category of 25- 39 years was the commonest age group involved [659 (36.5%)] followed by 15-24 years group [582 (32.2%)]. Males were almost twice (65.8%) in number compared to females (34.2%). The top three reasons for the ER visit were road traffic accidents (RTAs) [757(41.94%)], physical assaults [356 (19.72%)] and poisoning [239 (13.24%)]. Other causes were burns, falls, sexual assaults, hanging, injuries (gunshot, electrical and machinery) and drug overdose. Conclusion There are significant numbers and wide varieties of medico-legal cases that present in the ER of TUTH. Young males are the high-risk population and RTAs are the commonest etiology. This study will help the hospital in capacity strengthening of the ER, based on the volume of individual case types.